1996
DOI: 10.1182/blood.v88.11.4296.bloodjournal88114296
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and p53 mutations in therapy-related leukemia suggest mutator phenotype

Abstract: During the last decade the frequency of therapy-related acute leukemia (t-leuk) and myelodysplastic syndrome (t-MDS) has been increasingly observed. Over the past 15 years, we treated 56 patients with t-leuk who had received prior chemotherapy (39%), radiotherapy (11%), or both (45%). The drugs received included alkylating agents and topoisomerase II inhibitors. The primary tumors included hematological malignancies (49%) and solid tumors such as breast or ovarian cancer. The median age at diagnosis of the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
31
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…This finding is supported by the results of two other studies that demonstrated an association between MSI and abnormalities of chromosomes 5 and 7 (Ben-Yehuda et al, 1996;Horiike et al, 1999). This association could, in part, be explained by the high incidence of p53 mutations seen in these cases (Ben-Yehuda et al, 1996;Zhu et al, 1999) as it has been demonstrated that deficiencies in wild-type p53 may allow unrepaired double strand DNA breaks to contribute to the development of chromosomal instability (Honma et al, 2000). Our results differ from those of Rimsza et al (2000) who have analysed the largest series of cases of AML, also using a fluorescent PCR-based technique.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This finding is supported by the results of two other studies that demonstrated an association between MSI and abnormalities of chromosomes 5 and 7 (Ben-Yehuda et al, 1996;Horiike et al, 1999). This association could, in part, be explained by the high incidence of p53 mutations seen in these cases (Ben-Yehuda et al, 1996;Zhu et al, 1999) as it has been demonstrated that deficiencies in wild-type p53 may allow unrepaired double strand DNA breaks to contribute to the development of chromosomal instability (Honma et al, 2000). Our results differ from those of Rimsza et al (2000) who have analysed the largest series of cases of AML, also using a fluorescent PCR-based technique.…”
Section: Discussionsupporting
confidence: 83%
“…We found a high incidence of adverse-risk cytogenetics, including abnormalities of chromosomes 5 and 7, in the group of patients with MSI and, although these numbers were too small to allow for accurate statistical analysis, they suggest an association between cytogenetic risk group and MSI and, hence, aberrant DNA repair. This finding is supported by the results of two other studies that demonstrated an association between MSI and abnormalities of chromosomes 5 and 7 (Ben-Yehuda et al, 1996;Horiike et al, 1999). This association could, in part, be explained by the high incidence of p53 mutations seen in these cases (Ben-Yehuda et al, 1996;Zhu et al, 1999) as it has been demonstrated that deficiencies in wild-type p53 may allow unrepaired double strand DNA breaks to contribute to the development of chromosomal instability (Honma et al, 2000).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations